The shrub density effect: unraveling vertebrate community dynamics along an aridity gradient in Southern California - Zuliani, Mario; Ghazian, Nargol; MacDonald, Suzanne E.; Lortie, Christopher J. (Frontiers in Ecology and Evolution, 2025)
Foundational shrub species can support vertebrate communities within desert ecosystems. These shrubs provide thermal refuge to aid in temperature amelioration and to escape predation. Within Southern California, USA, harsh abiotic conditions influence the frequency of these shrub-animal interactions. We tested the hypothesis that increasing shrub density will positively influence local vertebrate communities across a variety of arid ecosystems within Southern California. We used a combination of camera trapping and temperature pendants across a 2-year field study to assess the effects of shrub density and near-surface air temperature on vertebrate community composition. Sites were established across Southern California, each consisting of four 20 m radius microsites, with shrub densities ranging from 0 to 14 individuals. Increasing shrub densities significantly increased the frequency of observation and richness of local vertebrate communities. Relatively higher near-surface air temperatures (NSAT) significantly decreased vertebrate observations, richness, and evenness. Sites with relatively higher annual aridity negatively influenced vertebrate species observations and richness, but could be offset by increasing shrub densities. While shrub encroachment in many ecosystems may have negative impacts on species biodiversity, our findings suggest that increasing densities of foundational shrub species positively influences vertebrate community measurements and composition across varying arid ecosystems. Understanding how these foundational shrub species can be used to assess vertebrate communities can provide key insight into vertebrate-shrub interactions and how these densities can shape the biodiversity of an ecosystem.